(Oligo-)Thiophene Functionalized Tetraazaperopyrenes: Donor-Acceptor Dyes and Ambipolar Organic Semiconductors - Hahn, Lena; Hermannsdorfer, André; Günther, Benjamin; Wesp, Tobias; Bühler, Bastian; Wadepohl, Hubert; Gade, Lutz H. (The journal of organic chemistry, 2017)
Tetraazaperopyrenes (TAPPs) have been functionalized with thiophene and terthiophene units of diﬀerent architecture resulting in a variety of organic donor−acceptor (D−A) compounds. The inﬂuence of the connection of the thiophenes to the TAPP core on their structural, photophysical and electrochemical properties has been studied in detail by a combination of X-ray crystallography, UV−vis and ﬂuorescence spectroscopy as well as cyclic voltammetry, which allowed the establishment of structure−property relationships. The HOMO−LUMO gap is signiﬁcantly decreased upon substitution of the TAPP core with electron-donating thiophene units, the extent of which is strongly inﬂuenced by the orientation of the thiophene units. The latter also crucially directs the molecular packing in the solid. Linkage at the α-position allows both inter- and intramolecular N···S interaction, whereas linkage in the β-position prevents intramolecular N···S interaction, resulting in a less pronounced conjugation of the TAPP core and the thiophene units. The new TAPP derivatives were processed as semiconductors in organic thin-ﬁlm transistors (TFTs) that show ambipolar behavior. The insight into band gap and structure engineering may open up new possibilities to tailor the electronic properties of TAPP-based materials for certain desired applications.